2017
DOI: 10.1177/0272989x17704858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti- Versus Pro-Vaccine Narratives on Responses by Recipients Varying in Numeracy: A Cross-sectional Survey-Based Experiment

Abstract: Purpose To inform their health decisions, patients may seek narratives describing other patients' evaluations of their treatment experiences. Narratives can provide anti-treatment or pro-treatment evaluative meaning that especially low-numerate patients struggle to derive from statistical information. Here, we examined whether anti-vaccine (vs. pro-vaccine) narratives had relatively stronger effects on the perceived informativeness and judged vaccination probabilities reported among recipients with lower (vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Older age was unrelated to motivation to think hard about complex problems and numeracy. As discussed in more detail below, the latter is in line with other studies of relatively educated samples (Bruine de Bruin et al, ; Låg et al, ; McNair et al, in press; Sinayev et al, ; Weller et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Older age was unrelated to motivation to think hard about complex problems and numeracy. As discussed in more detail below, the latter is in line with other studies of relatively educated samples (Bruine de Bruin et al, ; Låg et al, ; McNair et al, in press; Sinayev et al, ; Weller et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…As a result, the range of numeracy scores may have been restricted, thus limiting our ability to uncover correlations of numeracy with, say, age (see also Sinayev et al, ). Other studies with relatively educated samples have also found no significant correlation between numeracy and age (Bruine de Bruin et al, ; Låg et al, ; McNair et al, in press; Sinayev et al, ; Weller et al, ). Yet the tradition to recruit younger adults from among college students and older adults from the community may have confounded older age with lower educational attainment and therefore exaggerated the correlation between older age and lower numeracy skills (Strough, Parker, & Bruine de Bruin, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Decisions of the less objectively numerate instead are more vulnerable to decision heuristics, mental shortcuts used in judgments and choices (21)(22)(23). For example, they succumb to framing effects and the compelling power of narratives, emotions, and concrete, easy-to-evaluate information (24)(25)(26). As a result, the less objectively numerate tend to make worse decisions when numbers are involved, even after controlling for nonnumeric intelligence.…”
Section: Objective Numeracy and Numeric Confidence Have Separatementioning
confidence: 99%
“…that make them especially "sticky" in human minds [60]. Importantly, the same characteristics of these messages might also be used to promote vaccination [20,61], providing a more optimistic prospect for countering anti-vaccination information.…”
Section: Resultsmentioning
confidence: 99%